Economic and Policy Factors Affecting Palm Oil Export Value in Riau Province - Nizar, Rini; Gunawan Bahar, Erick (JURNAL AGRIBISAINS, 2026)
The palm oil industry is a strategic sector in Indonesia’s economy that contributes significantly to national income, employment creation, and energy diversification. Riau Province, as one of the largest producers of crude palm oil (CPO), plays an important role in supporting Indonesia’s export performance. However, fluctuations in export value are influenced by various internal and external factors, including international prices, exchange rates, land area, production volume, and government policies. This study aims to analyze the influence of economic factors and regulatory policies on the export value of CPO at both the provincial (Riau) and national levels. The research applies a multiple linear regression model using annual secondary data from 2013 to 2022 obtained from the Central Statistics Agency (BPS), the Directorate General of Plantations, and the World Bank. The results show that international prices and land area significantly affect CPO export value, while production and exchange rates have no significant influence. Strategic policies such as the Indonesian Sustainable Palm Oil (ISPO) certification, moratorium on new permits, and fiscal incentives have a positive but statistically insignificant short-term impact. The findings imply that Indonesia’s CPO export growth is mainly driven by global market dynamics and land capacity. Therefore, consistent and integrated sustainable policy support is essential to enhance competitiveness and ensure long-term export stability.